Innovative revenue strategies for physical education institutions: memberships, events, and e-commerce - Marchenko, Kateryna; Poliakova, Oksana (Національний технічний університет "Харківський політехнічний інститут", 2025)
It analyses how physical education institutions – such as schools, universities, sports academies, and fitness centers – can generate revenue through innovative business models.
Keywords: revenue; innovative strategies; physical education; business; health; fitness; active lifestyles; public institutions